2013
DOI: 10.1177/0003319713502120
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Epicardial Adipose Tissue With Arterial Compliance and Stiffness in Patients With Hypertension

Abstract: The main aim of the present study was to investigate the association between epicardial adipose tissue (EAT) and arterial function in patients with asymptomatic hypertension. Patients with hypertension (n = 155) were enrolled consecutively. Patients with decreased arterial compliance (AC) and increased cardioankle vascular index (CAVI) had higher EAT values compared with those with normal AC and CAVI (6.23 ± 1.67 vs 4.91 ± 1.40, P < .001 and 6.02 ± 1.61 vs 4.96 ± 1.46, P = .01, respectively). Analysis using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 34 publications
0
7
0
2
Order By: Relevance
“…EAT also plays an important role in the inflammatory process in the cardiovascular system via its endocrine and paracrine activity (6,15) . Several studies showed that EAT is associated with a variety of disorders such as atherosclerosis, xanthelasma palpebrarum, hypertension, arterial stiffness, enlarged atrial and ventricular dimensions, ventricular premature beats, atrial fibrillation, and increased LV mass (16)(17)(18)(19)(20) . Some potential mechanisms can be proposed to explain relationship between EAT and fQRS.…”
Section: Discussionmentioning
confidence: 99%
“…EAT also plays an important role in the inflammatory process in the cardiovascular system via its endocrine and paracrine activity (6,15) . Several studies showed that EAT is associated with a variety of disorders such as atherosclerosis, xanthelasma palpebrarum, hypertension, arterial stiffness, enlarged atrial and ventricular dimensions, ventricular premature beats, atrial fibrillation, and increased LV mass (16)(17)(18)(19)(20) . Some potential mechanisms can be proposed to explain relationship between EAT and fQRS.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies investigated the association of EAT-t with the grade of hypertension 12,30 . Additionally, four studies reported the association of cardiac remodeling and function with EAT 15,26,51,52 ,and three studies provided data addressing the association of ASCVD with EAT in hypertensive patients 15,28,53 .…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…It secretes numerous cytokines including adipocytokines, chemokines and interleukins, mediating unfavorable metabolism and proin ammatory activities 9 , which is involved in the pathophysiology of obesity-related heart diseases, including coronary artery disease, heart failure, atrial brillation, and carotid plaque 10 . There is growing evidence suggesting the association between EAT and EH [11][12][13][14][15] . EAT was increased in patients with EH compared with normotensive individuals [16][17][18] , and the incidence of hypertension was increased in subjects with higher amount of EAT 12 .…”
Section: Introductionmentioning
confidence: 99%
“…EAT has been also associated with markers of subclinical atherosclerosis. In this context, EAT was positively correlated with arterial stiffness (assessed by both pulse wave velocity and cardio-ankle vascular index) ( 10 , 11 ), and negatively with flow-mediated dilatation (FMD) ( 12 ). Furthermore, EAT has been positively related to CIMT in several patient populations, including those with T2DM, NAFLD, and MetS, ( 13 15 ) as well as in children and adolescents ( 16 ).…”
mentioning
confidence: 99%
“…Lifestyle interventions and certain drugs, such as anti-obesity (orlistat), hypolipidemic (statins, ezetimibe), and antidiabetic (metformin, pioglitazone, liraglutide, and exenatide) may improve abnormal adiposity ( 9 ). Apart from CV risk, EAT has been linked to markers of subclinical atherosclerosis, including arterial stiffness, FMD, CIMT and carotid plaques ( 11 13 , 18 ). As it can be easily measured during echocardiography, EAT represents an attractive surrogate to assess subclinical atherosclerosis, as well as drug effects on CV risk in clinical practice ( 19 ).…”
mentioning
confidence: 99%